(untitled) (International Journal of Information Technology and Computer Engineering, 2021)
Heavy metal pollution in aquatic water bodies from the release of toxic heavy metals from factories is a major problem in the modern world. Heavy metal pollution can be fixed in a number of ways, both physically and chemically. Biosorption is seen as a possible alternative to other methods for removing heavy metals from waste water. In this study, the peels of Citrus aurantifolia were used to remove Cu(II), Cr(VI), Pb(II), and Zn(II) ions from aqueous solutions. All four of the metal ions that were studied could be taken up by the peels. It was found that the biosorption process was affected by things like contact time, temperature, pH, turbidity, and the amount of biosorbent used. E-SEM, EDAX, and FT-IR analysis were also used to look at how Citrus aurantifolia changed after the biosorption process. The studies of adsorption isotherms showed that the Freundlich isotherm model fit experimental data better than the Langmuir isotherm model did. From a statistical point of view, the results were found to be important. By using certain eluents in a desorption study, biosorbent was brought back to life.